Enhancing Javanese Serang Speaking Skills through Series Picture Media in Primary Education - Sulasiah, Siti; Juhji, Juhji; Hasbullah, Hasbullah; Mastoah, Imas; Maksum, Ali (Journal of Asian Islamic Educational Management (JAIEM), 2025)
This study investigates the effectiveness of a series of picture media in enhancing the Javanese Serang speaking skills of first-grade students at SDIT Bina Insan. Six teachers and twenty students participated in semi-structured interviews and classroom observations over four weeks to gather data using a qualitative research approach. The effect of the media on pupils' speaking development was investigated using thematic analysis. The findings reveal notable improvements in pronunciation, vocabulary usage, and student participation during speaking activities. Additionally, students showed increased enthusiasm and engagement during Javanese language lessons. These results suggest that series picture media, with its colourful and contextually rich illustrations, is an effective pedagogical tool for promoting active language use and learner motivation. The study concludes that integrating visual-based media in early-grade language instruction can enhance language acquisition. It is recommended that educators incorporate such media to foster communicative competence and maintain learner interest in local language education.